Hubungan Pengetahuan dan Sikap terhadap Tindakan Pemilihan Obat Untuk Swamedikasi - Madania, Madania; Sy. Pakaya, Mahdalena; Papeo, Pirdawati (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
One of the curative efforts often carried out by the community is self-medication. Self-medication is one of the efforts in treating symptoms of illness or illness that is being suffered by someone without consulting a doctor in advance. Self-medication in its implementation cannot be separated from the use of traditional medicine and modern medicine. This study aimed to measured the correlation between the knowledge and attitude of the people of Tontulow village, North Sulawesi, regarding the tradisional medicine and modern medicine towards their act of selecting the type of medicine for self-medication. This study was an observational study with a cross sectional design. The sampling technique was performed by cluster sampling method. The instrument of the study was using questionnaire. For normality tes used Klomogrov-Smirnov test while for the correlation test used Pearson test. The number of participants were 83 respondents. Most of the people of Tontulow village have a sufficient level of knowledge regarding the traditional medicine and modern medicine, as many as 67 respondents (80.7%) with their attitude tended to be positive towards both medicine type. There was a correlation between knowledge and attitude regarding the tradisional medicine and modern medicine towards the act of selecting medicine type (the result of Pearson test: significance value less than 0,05)